Satisfaction of Patients Treated in Physical Medicine and Rehabilitation Department in CNHU-HKM of Cotonou - ALAGNIDE, HOUNTONDJI ETIENNE; NIAMA NATTA, DIDIER; HOUNGBEDJI, GERMAIN; ADIDO, MIREILLE; OLOUKA, JEAN; Havyarimana, ERIC; KPADONOU, GODONOU TOUSSANT (My University, 2018)
Abstract Satisfaction of patients is an important dimension of the hospital management and the evaluation of the quality of care and services offered to patients. Objective: To estimate the degree of satisfaction of patients admitted in Physical Medicine and Rehabilitation Department in the National Hospital and University Center (CNHU-HKM) in Cotonou. Method: Cross-sectional study with descriptive and analytical aim. It was led from June 15th to October 15th 2013, on 158 patients or guides of children or not communicating patients having ambulatory care in the Department of Physical Medicine and Rehabilitation and who agree to participate to the study. The level of global satisfaction of the subjects was estimated with a digital scale from 0 to 10. It was secondarily transformed into a discreet qualitative variable. Result: Rate of participation was 63.2%. Patients had deficiencies of rheumatilogical origine (41.1%), neurological (27.2%), traumatological (24.1%). Their pathologies were evolving since 1 month to 10 years. It was about their first attendance of the Rehabilitation Department of CNHU-HKM in 72.2%. Patients’ degree of satisfaction was good for the deadliness of expectation, reception (80%), cleanliness of the building, respect of patients’ intimacy. Global satisfaction of patients was good in 72%. It was influenced by the deadline of evolution of the pathologies. Discussion-Conclusion: The level of satisfaction of patients admitted in the Rehabilitation Department in CNHU-HKM was acceptable. However, they are parameters that remain to be improved.
Keywords: Satisfaction; Hospital Care; Rehabilitation; Cotonou